Response to Radioiodine Therapy for Thyrotoxicosis: Disparate Outcomes for an Indigenous Population - Jade A. U. Tamatea; John V. Conaglen; Marianne S. Elston (International Journal of Endocrinology)
Despite 70 years of experience treating thyrotoxic patients with radioiodine not all patients are successfully treated by a single dose. Multiple factors predicting radioiodine efficacy have been reported. The aim of this study was to assess whether ethnicity was associated with radioiodine response. A retrospective review was performed of patients who received radioiodine therapy for thyrotoxicosis from 1 January 2008 to 31 December 2010 and had follow-up available of a minimum of 12 months. 224 patients were included, 82.4% female, and 63.7% had Graves’s disease. Radioiodine failed in 21.5% of patients overall, with a higher failure rate in the indigenous population (35.2%). When controlling for other influencing factors by logistic regression, there continued to be an increased risk for the indigenous group (OR 2.82) and those treated with antithyroid drugs following radioiodine (OR 2.04). Younger age was also associated with an increased risk of failing radioiodine therapy (OR 0.97 for each year of age). Cure rates following radioiodine were lower for indigenes independent of factors known to affect radioiodine outcome. This is the first report demonstrating ethnicity as a possible independent variable for radioiodine efficacy. Further work is needed to investigate the cause of this difference.